CO-Ordinated Action Design of Rheostatic and Air Brakes on the Electric Railcar Series 6 111 - Zavada, Josip; Pajić, Zvonimir; Blašković, Jasna (Promet - Traffic&Transportation, 2012)
The paper presents the solution for the modification of thebrakes on the electric railcar series 6111 used in suburban traffic.It also gives the results of the performed measurements aswell as their analysis.The mentioned electric railcar is fitted with air and rheostaticbrakes whose activation is mutually independent. Sincesuburban traffic means frequent slopping, and since the enginedriver does not use the rheostatic brake regularly, but only theair brake, the wear of the brake lining and wheels is higher, andthe heat load on the brake elements is substantial. By regularapplication of rheostatic brake, the air brake could be LLSed lessthus contributing to a lower wear of the friction elements.The presented solution for the modification of the brakeconsists of co-ordinated and automatic action of the rheostaticand air brake with every braking